Hubungan Kausalitas Antara Ketahanan Pangan Dengan PDRB Kabupaten/Kota Di Jawa Tengah Tahun 2014 - Biantoro, Juli; , Didit Purnomo, SE., M.Si (2017)
Food security is the availability of sufficient world food in all the time to maintain the sustainability of food consumption, and balance the fluctuations in production and prices. Food security in General has four aspects, namely, include availability of food, outreach, stability and quality of consumption. On this research will be focused on the availability of food. As for the purpose of this research is to know how to influence the contribution food security against gross domestic product (GDP) Vice versa. Model analysis tools in this research will be tested using the test of causality analysis Granger which is a method to find out where on the one hand a dependent variable (the variable is not free) can be affected by other variables (the independent variable) and the independent variables on the other hand can occupy the position of the dependent variable. Such a relationship is referred to as the relation of causality or reciprocal links. Granger causality tests can noted that causality between the variables of food security and gross regional domestic product (GDP) per capita of mutual effect significantly.